(untitled) (Research, Society and Development, 2021)
There is a discrepancy in literature about the identification of species from Desmanthus genus. The aim was to characterize anatomically three genotypes representing Desmanthus pernambucanus (7G, 50J) and D. virgatus (13AU) species. The material was collected in experimental field of the Academic Unit of Serra Talhada (UAST/UFRPE) in dry season. Leaves of different ages were collected and fractionated into petiole, extrafloral nectary, rachis, petiolule and leaflet, following the slide preparation. Petiole morphology varied among genotypes and leaves studied. Extrafloral nectary is calyx-shaped whereas petiolule showed similar morphology in all genotypes. Rachis had similar morphology in 7G and 50J, for both leaves showing upper projections containing vascular bundles, whereas 13AU genotype showed a cylindrical shape. The leaflet showed a single layer of epidermal cells and dorsiventral mesophyll, except in young leaflets of 7G and 50J genotypes. It was observed secretory cavities in phloem at all fractions, except in the leaflets. There are anatomical and morphological features that may be useful to distinguish the studied species.